2015
DOI: 10.1038/nmat4401
|View full text |Cite
|
Sign up to set email alerts
|

Control of hierarchical polymer mechanics with bioinspired metal-coordination dynamics

Abstract: In conventional polymer materials, mechanical performance is traditionally engineered via material structure, using motifs such as polymer molecular weight, polymer branching, or copolymer-block design1. Here, by means of a model system of 4-arm poly(ethylene glycol) hydrogels crosslinked with multiple, kinetically distinct dynamic metal-ligand coordinate complexes, we show that polymer materials with decoupled spatial structure and mechanical performance can be designed. By tuning the relative concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
435
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 424 publications
(467 citation statements)
references
References 33 publications
14
435
2
3
Order By: Relevance
“…3,4 Especially the variety of available non-covalent bonds which can be used to form transient connections and therefore supramolecular polymers and networks is nowadays large. This broad variety of different interactions includes p-p stacking, 5,6 metal-ligand interactions, [7][8][9][10] hydrophobic forces, 11,12 electrostatic effects, 13,14 and hydrogen bonding. 4,[15][16][17][18][19][20] Not only the functionalization of the precursor building blocks (telechelic units) for the polymer chains and networks is today synthetically quite feasible, 21,22 but also the post modification of a polymer along the chain.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Especially the variety of available non-covalent bonds which can be used to form transient connections and therefore supramolecular polymers and networks is nowadays large. This broad variety of different interactions includes p-p stacking, 5,6 metal-ligand interactions, [7][8][9][10] hydrophobic forces, 11,12 electrostatic effects, 13,14 and hydrogen bonding. 4,[15][16][17][18][19][20] Not only the functionalization of the precursor building blocks (telechelic units) for the polymer chains and networks is today synthetically quite feasible, 21,22 but also the post modification of a polymer along the chain.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] One important subset of dynamic mechanical properties is the self-healing ability after mechanical damages. [8][9][10][11][12][13][14][15][16] The combination of mechanophore with luminescence can further endow materials with selfreporting damage detection property [17][18][19] and novel bio-mimic electronics with multifunctionalities. 20,21 The macroscopic dynamic mechanical properties of materials rely on the incorporated dynamic bonding at molecular levels.…”
mentioning
confidence: 99%
“…The elastic modulus, E > 3.5 GPa, of the bioinspired composites we present here is substantially (up to a million fold) stiffer than those tough elastomers found in literature. [46,47] This study thus demonstrates the utility of mussel-inspired dynamic bonding for processing a wide range of practical polymeric interfaces, including structural, load-bearing materials.…”
mentioning
confidence: 74%
“…[43] However, in man-made systems these toughening phenomena have been shown only in relatively soft materials to date. For example, although it has been recently reported that sample toughness increases can be achieved with the addition of catechol-mediated dynamic bonds [46] and double networks, [47] these studies have been limited to hydrogels and elastomers, where the elastic modulus E is less than 300 kPa. [48] In this study, we present significant toughness enhancement of a highly rigid synthetic polymer resin composite by a biologically inspired adhesive primer, providing strong and dynamic binding.…”
mentioning
confidence: 99%